Palisades Park - Brennert, Alan (New York : St. Martin's Press, 2013)
Here is a literate, thoughtful saga covering half a century in the life of a family whose world centers on a New Jersey amusement park.
Keywords: Working class families -- Fiction; Palisades Amusement Park (N.J.) -- Fiction; Depressions -- 1929 -- Fiction; Pearl Harbor (Hawaii), Attack on, 1941 -- Fiction; Conflict of generations -- Fiction; New Jersey -- Fiction; Domestic fiction